Neuroendocrine differentiation in a metachronous metastatic deposit in a case of mature growing ovarian teratoma: A rare occurrence - Divakar Jain; Shraddha Patkar; Jasmine Agarwal; Santosh Menon; Mahesh Goel (Indian Journal of Pathology and Microbiology)
Growing teratoma syndrome is a rare condition seen in non seminomatous germ cell tumor after completion of chemotherapy. Ectodermal, mesodermal and endodermal differentiation is commonly seen in mature teratoma. neuroendocrine differentiation in a metastatic deposit of mature teratoma is rarely reported. We are presenting a case of neuroendocrine differentiation in a long standing metastatic deposit of a mature teratoma.